An Efficient Fine-Grained Access Control Scheme Based on Policy Protection in SGs - Xiaoqing Guo; Huayi Wu; Zhen Qin; Ruonan Ying; Jilai Yang (IEEE Access, 2025)
With the rapid advancement of smart grid technology, data sharing between grid devices and between the grid and users has become increasingly frequent. This data sharing plays a crucial role in improving power system stability, optimizing energy distribution, and enhancing energy efficiency. However, the incomplete concealment of access policies during smart grid data sharing raises significant privacy concerns. We propose an efficient fine-grained access control scheme for secure information processing with policy protection to address this issue. By integrating the cuckoo filter, the proposed scheme achieves complete attribute hiding, thereby improving system privacy and security. We introduce an efficient attribute localization algorithm to address the complexity of attribute localization and recovery. Furthermore, blockchain technology is incorporated to support the revocation of secure data through signature verification. Security analysis demonstrates that the proposed scheme meets the defined security requirements, while performance evaluation indicates that it incurs minimal computational overhead while achieving enhanced privacy protection.